Punitiveness: A Philosophical Perspective. (August 2020) - Jacobs, Jonathan
In what respects can philosophical consideration of punitiveness as a sentiment, an attitude, and a motive illuminate whether there is a proper role for it, especially in regard to the context of criminal justice? Clearly, there are ways in which punitiveness can be excessive and needlessly harming. Are there also ways in which it can be felt and expressed in proper measure, or respects in which it is merited? Some of the distinctive harms of punitiveness are explicated, but it is shown that it is not always, or necessarily, morally problematic or objectionable. In fact, it can have an important role in preserving the civility of society.